Consumer Behavior as a Consequence of Social Networking Commercialization concerning the Contribution of Social Media Marketing Engagement and the Consumer Experience: A Case Study in Bangladesh - Md Azam Ali (ORGANIZE: Journal of Economics, Management and Finance, 2025)
Consumer behavior is the significant topic of social network commercialization in the overworld.The purpose of this paper is to investigate the impact that social media marketing involvement has had on the consumer experience in Bangladesh.There has been conducted for this research both qualitative and quantitative methodology. It has been analyzed by ArcGIS and Microsoft, where it creates a study area map, and most of the data has been analyzed in percentage, descriptive statistics, bar chart, and graph chart. It's all graph data that has been proven by linear regression analysis. The findings show that consumer income has the highest percentage at 32.142, and Facebook has the highest platform measurement at 42.619.The highest measure is the consumer purchase ratio, sometimes 37.857, and its output is the highest mean, 97.5; the consumer satisfaction ratio that was mostly satisfied measured 32.142. While somebody trusts that social media marketing makes shopping easier and more convenient, the highest measured 32.142 were satisfied. It uses those data as a case study and shows the preliminary findings of consumer association and clustering for each cluster. Additionally, it examines its results to see how it may use analytics to forecast consumer behavior going forward.